PELAKSANAAN KEWENANGAN DPRD DALAM ANGGARAN BIDANG PENDIDIKAN DI DKI JAKARTA PERIODE 2022-2023 : Implementation of DPRD Authority in the Education Budget in DKI Jakarta for the 2022-2023 Period - Pani, Nabilah Mutiara; Purnomowati, Reni Dwi (Faculty of Law, Universitas Trisakti, 2024)
One of the duties of the DKI Jakarta DPRD in preparing and stipulating the APBD in collaboration with the local government, in this case the Regional Head, is the budget function. Basically, the budget function plays an important role in funding all initiatives planned by the government aimed at improving the community's economy and realizing its welfare. The purpose of writing this thesis is to find out the mechanism for determining the education budget in the DKI Jakarta APBD and to find out the obstacles experienced by the DKI Jakarta Provincial DPRD in exercising the authority of the budget function in the field of education. Based on the results of the research, it is found that the organization of the education sector is an obligation of the local government. The implementation of the budget function until the 3rd quarter of the local government has run programs in education management and education support programs. Although, in its implementation there are still errors in distribution. The obstacles faced by the DKI Jakarta Provincial DPRD in carrying out its budget function authority include the Covid-19 pandemic factor, individual factors, political knowledge factors, DPRD members' knowledge of the budget, and the lack of complementary data in carrying out the budget function..